APPLICATION OF HOMEROOM GUIDANCE METHODS IN IMPROVING STUDENT'S LEARNING ACHIEVEMENT - Rusman C Rumegang (Educouns Journal: Jurnal Pendidikan dan Bimbingan Konseling, 2020)
The research objective was to monitored the implementation of home guidance in improving student achievement in class VIII at State Junior High School 3 Tondano. This research was a counseling action research with four stages: planning, implementing, observing, and reflecting. The research subjects were seven people who had low learning achievement. Data were collected by using two methods of observation and interviews. Data analysis used qualitative data analysis, data reduction, data display, and data collection. The results showed that the homeroom method could improve student achievement with two cycles of application time.